Persistence of Social Exclusion among Older People in Australia: What are the protecting factors? - Yu, P; Miranti, R (My University, 2014)
The existing literature on social exclusion among older people, though relatively limited,suggests that disadvantage among the elderly is cumulative in nature. Some aspects of disadvantage starting at early life stages have long-term consequences. As such, older people with disadvantages may be subject to higher risks of persistent social exclusion. This paper aims to improve understanding of the persistence of social exclusion among senior Australians in three ways. Firstly, the incidence of social exclusion among older people is analysed using selected indicators. Secondly, the paper examines whether an older person experiencing social exclusion at one time is more likely to experience it again (persistence). Thirdly, it investigates what factors may be protecting older people from persistent social exclusion. The analysis is conducted using the first eight waves of the Household, Income and Labour Dynamics in Australia (HILDA) Survey (2001–2008). The sample of the elderly is disaggregated into a younger group (55-64 years at wave 1) and an older group (65+ years). Notwithstanding a low incidence of social exclusion (especially in multiple dimensions), the analysis indicates a relatively high persistence of exclusion: among less than 10 per cent of the sample of older people who experienced social exclusion in the previous year, about 45 per cent of that smaller group experienced the same situation in the following year. Further, the paper suggests that higher education and income, as well as better health conditions and previous employment experiences, are important protective factors from social exclusion for older people.
Keywords: Disadvantage -- Exclusion; Ageing; Life Events; Disadvantage, adversity and resilience; Disadvantage; Ageing; Life Events; Exclusion; Dsiadvantage, adversity and resilience; Adversity and resilience